Polynomial Modelling of Southern African Secular Variation Observations Since 2005 - P Kotzé; M Korte; M Mandea (Data Science Journal, 2011)
The COMPASS (COmprehensive Magnetic Processes under the African Southern Sub-continent) program forms part of a collaboration project between Germany and South Africa, called Inkaba ye Africa, and aims to investigate the regional geomagnetic field in this area, particularly its evolutionary behaviour. Results obtained from field surveys conducted by the Hermanus Magnetic Observatory (HMO) and the Helmholtz GeoForschungsZentrum (GFZ) in South Africa, Namibia, and Botswana, in addition to geomagnetic field data from the 4 continuous recording magnetic observatories in southern Africa at Hermanus, Hartebeesthoek, Keetmanshoop and Tsumeb, were used to model the geomagnetic field time variation by means of a polynomial approach.